2016
DOI: 10.5194/bg-2015-669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of ocean acidification on the structure and fatty acid composition of a natural plankton community in the Baltic Sea

Abstract: <p><strong>Abstract.</strong> Increasing atmospheric carbon dioxide (CO<sub>2</sub>) is changing seawater chemistry towards reduced pH, which consequently affects various properties of marine organisms. Coastal and brackish water communities are expected to be less affected by ocean acidification (OA) as these communities are typically adapted to high fluctuations in CO<sub>2</sub> and pH. Here we investigate the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Studies of natural assemblages of marine phytoplankton have found that high CO 2 resulted in an increase in the abundance of the cyanobacterium Synechococcus and a decrease in the abundance of the coccolithophore Emiliania huxleyi (Paulino, Egge, & Larsen, ). Similar experiments also found a decrease in fucoxanthin‐containing phytoplankton including diatoms (Yoshimura et al., ) or that community composition remains unchanged (Bermúdez et al., ). Within taxonomic groups, an increase in CO 2 benefits larger over smaller diatoms (Tortell et al., ) as expected from facilitation of CO 2 diffusion with larger surface area to volume ratios.…”
Section: Introductionmentioning
confidence: 60%
“…Studies of natural assemblages of marine phytoplankton have found that high CO 2 resulted in an increase in the abundance of the cyanobacterium Synechococcus and a decrease in the abundance of the coccolithophore Emiliania huxleyi (Paulino, Egge, & Larsen, ). Similar experiments also found a decrease in fucoxanthin‐containing phytoplankton including diatoms (Yoshimura et al., ) or that community composition remains unchanged (Bermúdez et al., ). Within taxonomic groups, an increase in CO 2 benefits larger over smaller diatoms (Tortell et al., ) as expected from facilitation of CO 2 diffusion with larger surface area to volume ratios.…”
Section: Introductionmentioning
confidence: 60%
“…For more detailed descriptions of the primary variables and the different methods used during this CO 2 mesocosm campaign, we refer to other papers in this joint volume: i.e., total particulate carbon (TPC), dissolved organic carbon (DOC), and dissolved inorganic carbon (DIC) are described by Paul et al (2015); micro-and nanophytoplankton enumeration by Bermúdez et al (2016); picophytoplankton, heterotrophic prokaryotes, and viruses by Crawfurd et al (2016); zooplankton community by Lischka et al (2015); primary production and respiration by Spilling et al (2016a); BP by Hornick et al (2016); and sedimentation by Boxhammer et al (2016) and Paul et al (2015).…”
Section: Primary Variablesmentioning
confidence: 99%
“…: every 4th day until t29; copepods: weekly (t3, t10, t17, t24, t31, t38) Almén et al (2015); Bermúdez et al (2015) Fatty acid concentrations (E. affinis adults and eggs from reproduction incubations)…”
Section: Gc-msmentioning
confidence: 99%